Evaluation of the Toxicopathological Lesions of Berberis Vulgaris Using a Chicken Embryonic Model: Toxicopathological Lesions of Berberis Vulgaris - Derakhshanfar, Amin; Tavakkoli, Hadi (Iranian Journal of Pharmaceutical Sciences, 2018)
Toxicopathological effects of herbs have been always a major concern. There is scant information available about the toxicopathological effects of barberry in the fetus. Since the embryogenesis in chicken is similar to human beings. The objective of this study is to evaluate the lesions of the various dosages of Berberis vulgaris using a chicken embryonic model. Fertile chicken eggs were divided into four equal treatment groups; phosphate buffered saline-injected group and barberry-injected groups whose individuals were injected with Berberis vulgaris fruit-extract at dosages of 10, 50 and 100 mg per Kg egg-weight, respectively. Embryos were re-incubated post-treatment and allowed to develop until day 18, after which they were examined for macroscopic and microscopic lesions. Results demonstrated that embryos were stunted in the barberry-injected groups. Defect in feather growth and general congestion was accompanied by pathological changes in brain, liver, kidney, heart, and lung. Histopathological lesions include congestion, hemorrhage, edema, and micro-thrombosis in the affected organs. Based on findings, it is concluded that Berberis vulgaris at the above-mentioned concentrations is toxic to the chicken embryo in a dose dependent manner. Further studies are needed to clarify the toxic effects of this herb on the development of human fetus.